An investigation into hypotactic and paratactic projection in english and vietnamese - a functional contrastive analysis - Trần Thị Thanh Hà (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In the light of Systemic - Functional grammar, based on the theories of a clause complex, this thesis is carried out in an endeavor to provide learners of English with an insight into Hypotactic and Paratactic Projection. With data from well-known books by Functional Grammarians and short stories by famous writers in English and Vietnamese, the researcher tries to point out some similarities and differences in both languages. By the end of the study, some practical implications are put forward. The findings of the study are hoped to benefit not only English teachers and learners but also those who are interested in linguistics.